Fire force. Volume 10, His brother's keeper - Ōkubo, Atsushi (Kodansha Comics, 2018)
"Shinra has found Shō; at last, and he's eager to rescue him from the clutches of the Evangelist. But Shō; has no memory of his older brother, and refuses to accept the possibility that the two of them are related. Shinra's only choice is to beat Shō; up and drag him home, but how can he defeat someone who has the power to stop time?"--Pg.4 of cover.